ANALISIS KEBERHASILAN PENGELOLAAN LEMBAGA PENDIDIKAN RAUDHATUL ATHFAL AL-HIDAYAH KECAMATAN TAMPAN KOTA PEKANBARU: Henri Yanto Daulay, Nurlaili - daulay, henri yanto; Nurlaili, Nurlaili (P3M STKIP 'Aisyiyah Riau, 2024)
The purpose of this study was to determine the efforts made by Al Hidayah Education Foundation in Tampan District, Pekanbaru City in advancing the Raudhatu lAthfal (RA) educational institution. To find out the management of education that is applied in the RA Al Hidayah educational institution so that it is in great demand by the community. To find out the factors that influence the success of RA Al Hidayah educational institutions in organizing the education process. The approach in this research is a qualitative approach. This approach was chosen with the consideration that researchers can examine more deeply about the symptoms, events and events in the environment experienced. Bogdan and Biklen in Sugiyono (2005: 9). The data collection technique is done by direct observation to the field and in-depth interviews with informants and the collection of physical evidence in the documentation. The results of the study are the efforts of the Al Hidayah foundation in achieving success cannot be separated from the implementation of the planning, organizing, directing and supervisory functions. The RA Al-Hidayah effort in improving the quality of education by developing education management namely (1) curriculum management. (2) teacher management. (3) student management. (4) Fund management system. And the success factor of RA Al-Hidayah in carrying out its function as an educational institution is inseparable from the strength of the organization in developing schools, human resources (all steak holders) RA Al-Hidayah and the existence of the local community.